ANALISIS PENANGANAN KEJAKSAAN NEGERI WONOGIRI DALAM UPAYA RESTORATIVE JUSTICE - Asti Giri Anjani; Rizal Aludya Danu Siswanto; Bondan Nugroho; Tri Astuti Kusumawati; Wahyu Prabowo (Cahaya Ilmu Bangsa, 2024)
The handling of Restorative Justice by the Wonogiri Prosecutor's Office in criminal acts is the main focus of this research. Restorative Justice is an alternative approach to the criminal justice system that focuses on restoring victims, perpetrators and society. This research aims to investigate the implementation of Restorative Justice by the Wonogiri Prosecutor's Office in handling crimes with light sentences. The research method used is qualitative research with data collection techniques through interviews, observation and document analysis. The research results show that the Wonogiri Prosecutor's Office has implemented various strategies in implementing Restorative Justice, such as mediation, group conferences, and rehabilitation programs. This approach provides space for victims, perpetrators and the community to actively participate in the conflict resolution process. However, there are several obstacles faced in implementing Restorative Justice by the Wonogiri Prosecutor's Office, including a lack of public awareness about the concept of Restorative Justice, limited human resources and budget, as well as challenges in measuring the success of the program. Therefore, further efforts are needed to increase public understanding and participation as well as improve infrastructure and human resources in the criminal justice system. It is hoped that this research can contribute to the development of Restorative Justice policies and practices at the local level, as well as becoming a basis for further research in this field.